Alterations in the vitamin D endocrine system during pregnancy: A longitudinal study of 855 healthy Norwegian women - Gustafsson, Miriam K. (PLoS One, 2018)
To ensure optimal calcium accrual in the fetal skeleton, a substantial rise occurs in 1,25-dihydroxyvitamin D (1,25(OH)(2)D), but is dependent on sufficient 25-hydroxyvitamin (25(OH)D). Large longitudinal studies addressing free 25(OH)D and 1,25(OH)(2)D during pregnancy are scarce. We aimed to assess levels of and relationship between 25(OH)D, 1,25(OH)(2)D, vitamin D-binding protein (DBP), parathyroid hormone (PTH), and free 25(OH)D during pregnancy; determinants of vitamin D status; and association between vitamin D indices or PTH and pregnancy outcomes (gestational diabetes mellitus and birthweight). Altogether 855 pregnant Norwegian Caucasian women from Trondheim and Stavanger (latitude 63°N and 58°N) were recruited; 94 were lost to follow-up. The study was originally a randomized controlled trial (2007–2009) with gestational diabetes as primary outcome. Data were collected in second and third trimester. In third trimester, 246 (34%) had vitamin D insufficiency and 52 (7%) deficiency (25(OH)D <50 and <30nmol/L, respectively). During wintertime in third trimester, 61 (47%) from Trondheim and 23 (51%) from Stavanger exhibited vitamin D insufficiency. PTH was elevated in 27 (3.7%). Estimate of change between trimesters was (95% CI): 25(OH)D -1.8 (-2.8 to -0.7) nmol/L, DBP 0.62 (0.57 to 0.66) μmol/L, calculated free 25(OH)D -1.7 (-2.0 to -1.4) pmol/L, PTH 0.81 (0.72 to 0.90) pmol/L, 1,25(OH)(2)D (sub-analysis) 31.4 (CI 24.7 to 38.2) pmol/L. A decrease in 1,25(OH)(2)D occurred in 45% of those with vitamin D deficiency, and they also exhibited lower levels than women with adequate vitamin D status. No association of vitamin D indices and PTH with pregnancy outcomes was observed. Women in Trondheim displayed lower 25(OH)D levels, despite minor latitudinal differences. Less than one-fifth adhered to the authorities’ vitamin D recommendations. These findings demonstrate that hypovitaminosis D is prevalent among pregnant women living in northern latitudes, especially during the dark season, and there is an unmet need to ensure adequate vitamin D intake.